Analisis Kesalahan Penulisan Surat Dinas: Studi Kasus di SMP Negeri 2 Sangatta Utara - Cindy; Ratna Dwi Ramdhani; Umi Kalsum; Juliana (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
The use of standard language in official letters can make understanding easier for readers. Communication via letters is an important form of written communication. Official letters, as a means of written communication between interested parties, have various important functions, including as a means of written communication, authentic evidence, historical evidence, ambassadors/representatives, and guidelines. This research uses a qualitative approach with a case study method to analyzing errors in writing official letters by teachers and staff at SMP Negeri 2 Sangatta Utara. In the letters that have been analyzed, there are several errors found ranging from formatting errors, errors in the use of spelling, punctuation, and word choice. This research shows that there are many errors in writing official letters for students at SMP Negeri 2 Sangatta Utara. This error is caused by several factors, including lack of understanding of teachers and staff, lack of training, lack of guidance, and lack of facilities and infrastructure. Therefore, efforts need to be made to overcome these errors, such as providing a deeper understanding, providing more practice in writing official letters, providing more intensive guidance, and providing adequate facilities and infrastructure.